Fluconazole for Hypercortisolism in Cushing’s Disease: A Case Report and Literature Review - Zhao, Yiming; Liang, Weiwei; Cai, Feng; Wu, Qun; Wang, Yongjian (Frontiers in Endocrinology, 2020)
Background Cushing’s disease is associated with an increased risk of pulmonary fungal infection, which could be a relative contraindication for pituitary adenoma excision surgery. Case We report a case of a patient with Cushing’s disease and pulmonary Cryptococcus neoformans. A 48-year-old woman was admitted to our hospital because of moon face and edema. Laboratory and radiological findings suggested a diagnosis of Cushing’s disease and pulmonary cryptococcus infection. Fluconazole 400 mg per day was administered intravenously and continued orally for 3 months. Both cryptococcus infection and hypercortisolism relieved and transsphenoidal resection was performed. Conclusion Cushing’s disease can be effectively treated with fluconazole to normalize cortisol concentration prior to pituitary surgery. Fluconazole is an alternative treatment especially in Cushing’s disease patients with cryptococcal pneumonia.